Sec3-containing Exocyst Complex Is Required for Desmosome Assembly in Mammalian Epithelial Cells - Andersen, Nicholas J. (The American Society for Cell Biology, 2010)
The Exocyst is a conserved multisubunit complex involved in the docking of post-Golgi transport vesicles to sites of membrane remodeling during cellular processes such as polarization, migration, and division. In mammalian epithelial cells, Exocyst complexes are recruited to nascent sites of cell–cell contact in response to E-cadherin–mediated adhesive interactions, and this event is an important early step in the assembly of intercellular junctions. Sec3 has been hypothesized to function as a spatial landmark for the development of polarity in budding yeast, but its role in epithelial cells has not been investigated. Here, we provide evidence in support of a function for a Sec3-containing Exocyst complex in the assembly or maintenance of desmosomes, adhesive junctions that link intermediate filament networks to sites of strong intercellular adhesion. We show that Sec3 associates with a subset of Exocyst complexes that are enriched at desmosomes. Moreover, we found that membrane recruitment of Sec3 is dependent on cadherin-mediated adhesion but occurs later than that of the known Exocyst components Sec6 and Sec8 that are recruited to adherens junctions. RNA interference-mediated suppression of Sec3 expression led to specific impairment of both the morphology and function of desmosomes, without noticeable effect on adherens junctions. These results suggest that two different exocyst complexes may function in basal–lateral membrane trafficking and will enable us to better understand how exocytosis is spatially organized during development of epithelial plasma membrane domains.